THE EFFECT OF RIDDLE GAME ON STUDENTS’ VOCABULARY MASTERY AT GRADE TEN OF SMK SWASTA HKBP PEMATANGSIANTAR - EVITA PARON SINAGA; SELVIANA NAPITUPULU; NOVRA MELISA P HUTABARAT (CV KULTURA DIGITAL MEDIA, 2022)
This research was aims to see effect of riddle game on students’ vocabulary mastery at grade ten of SMK Swasta HKBP Pematangsiantar. This research use 20 multiple choice with using pre-test and post-test in experimental and control group but different treatment. This research design was quantitative research. As experimental research, aimed to know the effect of techniques that given, whether in influenced to the object or not. The sample of this research took from two classes that consist of 56 students (28 students in experimental group in class X TBSM1 and 28 students in control group was X TBSM2).The researcher found that the mean of pre-test in experimental group was 80,16 and the mean of pre-test in control group was 56 and the research also found that t-test was higher than t-table. It showed from df:54 (28+28-2) with the table was 1,67 and the level of significances 0,05. It showed that t-test was higher than t-table (2,08> 1,67). Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Finally, the research concluded that there was significant effect of riddle game to the students’ vocabulary mastery at grade ten of SMK Swasta HKBP Pematangsiantar.